Extraction of coconut oil using galactomannanase - Candeloza, Andrean Salonga
ABSTRACT Extraction of oil from fresh coconut meat incorporating the use of galactomannanase was developed and evaluated. The moisture and fat contents of the coconut samples, extraction process, optimum concentration of galactomannanase and the physico-chemical characteristics of the extracted oil were determined. The extraction process involved enzyme treatment, pasteurization, freeze-thaw operation and heating. Optimum condition for the enzyme treatment of the fresh coconut meat was set at pH 4.5 and 55°C. The moisture and fat contents of the samples using Kitchen, Centrifuge and Freeze-thawing + heating methods were 33.52, 20.66, and 62.89%, respectively. Samples treated with 20 mg enzyme/ 100g substrate gave the highest oil yield of 67.86%. Galactomannanase-treated samples showed no significant difference in oil yield and were higher than the untreated samples. Results in the determination of free fatty acid content, acid value, iodine and saponification numbers of the extracted coconut oil fall within literature and standard values.